Dakwah Organizations in Pluralistic Community, Prospects and Challenges: A Case Study of Jamiyah Singapore - Andi Abdul Kadir Andi Kitta (Human Sustainability Procedia, 2018)
It is no doubt that our present world presents challenges to everyone who has conscience to work together to prevent a collapse of moral civilization and promote through all means possible, a 21st Century intellectual, moral and spiritual infrastructure for the sake of human and all creatures of God sustainability. Religion has, since the beginning of human society, been the basis of wholesome human civilization. This holistic guidance from Almighty Allah has always been disseminated through thousands of Prophets and Messengers of God who were sent to all ancient nations. Their messages, whether verbal or written down in the form of scripture were in perfect accordance with the socio-cultural, political, economic and intellectual development of different societies at different times. The essence of the universal values that were taught such as Reverence for God, filial piety, familial responsibility, chastity before, during and outside marriage, love for children, compassion for the less fortunate, neighbourliness, love of nation, striving for excellence, thrift, prudent, charity, valour and chivalry, sense of balance, appreciation of beauty given in the cultural format of the different societies sustained human civilization